Pemanfaatan E-LKPD Berbasis Web Lifeworksheet pada Materi Teks Prosedur Siswa Kelas 9 SMPN 5 Cibadak - Rulliawan, Soffan; Akhmad Yosep Pujiana; Sobri; Tatu Hilaliyah (Metakognisi, 2025)
The development of information technology has influenced all aspects of life, including the world of education. Information technology in the world of education is a necessity, one of which is the use of various learning applications. The aim of this research is to describe the use of live worksheet web-based E-LKPD in learning Indonesian on procedural text material. Researchers will describe how it is used, benefits, advantages, and challenges that may be faced in application. This research uses a qualitative descriptive approach that focuses on the use of live worksheets as a learning medium for procedure text material for class IXC students at SMPN 5 Cibadak. The results of this research indicate that live worksheet web-based E-LKPD can increase student activity in learning procedural texts. Students look enthusiastic in watching and reading the material. Students actively discuss when working on group worksheets, actively work on individual worksheets, and formative assessments of procedural text material. Live worksheet web-based e-LKPD can increase students' interest in learning. Students feel happy when learning Indonesian using procedure text material. Web-based e-LKPD live worksheets can also improve understanding of procedural text material. This can be seen from the increase of the average score 13.20 points, it’s from 62.48 to 75.68.